Intention to use e-wallet among Generation Z during COVID-19 - Risa Khairani; Vidyarini Dwita (Operations Management and Information System Studies, 2022)
This research intends to analyze the influence of perceived risk and government support on intention to use e-wallet among Gen Z in Padang during COVID-19 with perceived usefulness as a mediating variable. 150 respondents participated to this research, and SmartPLS analyzed the data. These study's conclusions included the following information (1) Perceived risk influences on perceived usefulness positive significantly. (2) Government support influences on perceived usefulness positive significantly. (3) Perceived risk influences on intention to use e-wallet positive significantly. (4) Perceived usefulness mediates the influence of perceived risk on intentions to use e-wallet positive significantly. (5) Government support influences on intention to use e-wallet positive significantly. (6) Perceived usefulness mediates the influence of government support on intentions to use e-wallet positive significantly. (7) Perceived usefulness influences on intention to use e-wallet positive significantly.